HUBUNGAN POLA KOMUNIKASI KELUARGA TERHADAP TINGKAT KESEPIAN (LONELINESS) PADA LANSIA - Amalia Sari; Herlina Herlina; Veny Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Elderly is the process of growth and development which at this time elderly will experience physical, mental and social decrease. Family is the closest person to the elderly who accompany the elderly in their old age. The purpose of this study was to determine the relationship between family communication with the level of loneliness in the elderly. This study used descriptive correlation and cross sectional approach. This study was conducted on 100 elderly from Payung Sekaki taken by using cluster sampling technique. The data analysis used was bivariate analysis by using Chi-Square test. Test showed there was a significant correlation between family communication patterns on the level of loneliness in the elderly with p value (0.000) < ɑ (0.05). There is a significant correlation between family communication pattern on the level of loneliness in the elderly. This research recommended that every elderly family member to apply a functional communication pattern to reduce the level of loneliness in the elderly.Keywords: Elderly, Communication, Family, Loneliness